The Role of Fair Value Accounting in Enhancing Financial Transparency in the Age of Digital Assets - Kekoto Manneh; Siti Sundari (International Journal of Economics and Management Sciences, 2025)
This literature review investigates the influence of fair value accounting (FVA) on enhancing financial transparency, particularly within the evolving context of digital assets. By analyzing 103 peer-reviewed articles, the study evaluates how FVA facilitates automated, real-time, and market-based disclosures. It identifies FVA as a tool for increasing investor trust and improving the clarity of financial statements by aligning valuations with current market conditions. The review also highlights the specific challenges of applying FVA to decentralized and volatile digital assets such as cryptocurrencies and non-fungible tokens (NFTs). Although FVA contributes to more transparent and relevant reporting, the implementation of FVA for digital assets is hindered by several critical issues. These include inconsistent valuation methodologies, lack of standardized regulatory guidance, susceptibility to market manipulation, and technological limitations in tracking asset value across decentralized platforms. Furthermore, the rapid pace of innovation in digital finance outstrips the adaptability of existing accounting standards and legal frameworks, creating a gap that weakens the consistency of fair value assessments. The review proposes the integration of FVA within a broader theory of decision-making under uncertainty, emphasizing the need for adaptive and digitization-responsive accounting practices. It suggests practical frameworks that align valuation procedures with the unique characteristics of digital assets while ensuring compliance with emerging regulations. This research encourages ongoing examination and policy innovation to ensure that FVA continues to support transparency and informed decision-making in a dynamic financial landscape.